2019
DOI: 10.1103/physrevmaterials.3.054802
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in single-crystalline aluminum- and gallium-hyperdoped germanium

Abstract: Superconductivity in group IV semiconductors is desired for hybrid devices combining both semiconducting and superconducting properties. Following boron doped diamond and Si, superconductivity has been observed in gallium doped Ge, however the obtained specimen is in polycrystalline form [Herrmannsdörfer et al., Phys. Rev. Lett. 102, 217003 (2009)]. Here, we present superconducting single-crystalline Ge hyperdoped with gallium or aluminium by ion implantation and rear-side flash lamp annealing. The maximum con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Moreover, the inset in Figure 3d shows that the diffusion of Sn can be fully suppressed using ms-range solid phase epitaxy. We have observed the same effect for other elements implanted into Ge, like Al, Ga, or P [6,7,25]. It is clear that, within the island, the Ge forms a continuous layer, but voids are well visible below the surface.…”
Section: Materials 2020 13 X For Peer Review 4 Of 10supporting
confidence: 74%
See 2 more Smart Citations
“…Moreover, the inset in Figure 3d shows that the diffusion of Sn can be fully suppressed using ms-range solid phase epitaxy. We have observed the same effect for other elements implanted into Ge, like Al, Ga, or P [6,7,25]. It is clear that, within the island, the Ge forms a continuous layer, but voids are well visible below the surface.…”
Section: Materials 2020 13 X For Peer Review 4 Of 10supporting
confidence: 74%
“…It has been shown that p-type doping in Ge is less problematic, while n-type doping remains challenging. Al or Ga that are implanted into Ge and subjected to rapid thermal annealing (RTA) for tens of seconds or flash lamp annealing (FLA) for milliseconds act as acceptors at hole concentrations above 10 21 cm −3 [4][5][6]. Such highly doped Ge exhibits superconductivity at critical temperatures below 1 K and it can provide excellent low resistive ohmic contacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Recently, we have shown that dopant diffusion in semiconductors can be significantly suppressed using strongly non-equilibrium thermal processing, e.g. ms-range FLA. [34][35][36] During FLA, the peak temperature is close to the melting point of the material to be annealed but never beyond. This ensures the recrystallization of the implanted layer via explosive solid phase epitaxy.…”
Section: Sample Fabricationmentioning
confidence: 99%
“…In its pure and alloyed state, Ge is used in a wide variety of roomtemperature electronics with high integrability with Si technology. Superconductivity in Ge is demonstrated through Ga + ion implantation followed by dopant activation via rapid thermal annealing (RTA) or flash lamp annealing (FLA) at temperatures near the Ge melting point (∼ 938 • C) 16,[21][22][23] . Such high temperatures were intended for recovering the crystallinity of the Ge substrate damaged by implantation.…”
Section: Introductionmentioning
confidence: 99%